Gender-specific impact of stress and adiposity on autonomic stress modulation in teachers - Álvarez-Gallardo, Estela; Calderón García, Andrea; Belinchón-deMiguel, Pedro; Clemente-Suárez, Vicente Javier (Frontiers in Psychology, 2025)
IntroductionTeaching is recognized as one of the most stressful professions, often leading to negative physical and mental health outcomes.ObjectiveThis study aimed to analyze the relationship between stress and adiposity in teachers, considering gender differences.MethodsA cross-sectional descriptive study was conducted with 253 teachers from compulsory and higher education during the 2022–2023 academic year. Autonomous regulation was assessed using heart rate variability, adipose tissue mass was measured with bioelectrical impedance analysis, and stress was evaluated through validated psychological questionnaires.ResultsMen with higher adiposity exhibited lower levels of Root Mean Square of the Successive Differences (RMSSD; 34.75 ± 14.49 vs. 47.25 ± 26.75, p = 0.015) and the number of pairs of intervals differing by more than 50 ms (pNN50; 12.31 ± 10.50 vs. 21.28 ± 17.96, p = 0.016), with a low-frequency (LF)/high-frequency (HF) band ratio of (4.72 ± 3.62 vs. 4.84 ± 3.48), suggesting greater sympathetic activation. In contrast, women with higher adiposity showed higher values in LF, HF, and the LF/HF ratio (3.13 ± 2.60 vs. 2.42 ± 2.33, p = 0.015), indicating a predominance of parasympathetic activity. Additionally, the group with a higher percentage of body fat had higher scores on the Perceived Stress Scale, the Maslach Burnout Inventory, the State Anxiety Questionnaire, and exhibited less extroverted personalities.Conclusionswe found that higher adiposity in teachers is linked to increased stress and altered autonomic regulation. Men with higher adiposity exhibited greater sympathetic activation, while women reported higher stress with more variable autonomic responses. These findings suggest the need for gender-specific interventions to address both the psychological and physiological components of stress in educators.